2011
DOI: 10.1111/j.1478-3231.2011.02483.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in the concentrations of ketone bodies in cirrhosis and hepatic encephalopathy: a study in patients with TIPSS

Abstract: There are significant variations in the regional concentrations of the ketone bodies in encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In a fasting state, ketone body is also one of energy substrates for total body tissue, especially in the brain. 38 Previous studies demonstrated that the concentration of ketone body is elevated in cirrhotic patients after starvation, in a similar manner to FFA. 26,27 In this study, there was a correlation between npRQ and ketone body in a fasting state (Table 3), but ketone body did not correlate with the Child-Pugh classification (Table 1).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a fasting state, ketone body is also one of energy substrates for total body tissue, especially in the brain. 38 Previous studies demonstrated that the concentration of ketone body is elevated in cirrhotic patients after starvation, in a similar manner to FFA. 26,27 In this study, there was a correlation between npRQ and ketone body in a fasting state (Table 3), but ketone body did not correlate with the Child-Pugh classification (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…Ketone body is synthesized mainly in the liver by β‐oxidation of FFA derived from the adipose tissue. In a fasting state, ketone body is also one of energy substrates for total body tissue, especially in the brain . Previous studies demonstrated that the concentration of ketone body is elevated in cirrhotic patients after starvation, in a similar manner to FFA .…”
Section: Discussionmentioning
confidence: 99%